2002
DOI: 10.1046/j.1526-4610.2002.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Gene Polymorphism in Migraine

Abstract: These data support the hypothesis that lymphotoxin alpha could be a susceptibility gene in migraine without aura and confirm previous data indicating that migraine with and without aura are distinct entities with different genetic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 27 publications
3
63
2
2
Order By: Relevance
“…Transitory increases in the levels of TNFa have been observed in the plasma of migraineurs (22 MO, 4 MA) [Perini et al, 2005] and in the internal jugular blood of migraineurs with aura [Sarchielli et al, 2006] during an attack. Analysis of TNFb polymorphisms suggested a role for TNFb in MO but not in MA [Trabace et al, 2002]. In a separate study, investigation of TNFa also showing an association with MO but not MA .…”
Section: Other Genesmentioning
confidence: 84%
“…Transitory increases in the levels of TNFa have been observed in the plasma of migraineurs (22 MO, 4 MA) [Perini et al, 2005] and in the internal jugular blood of migraineurs with aura [Sarchielli et al, 2006] during an attack. Analysis of TNFb polymorphisms suggested a role for TNFb in MO but not in MA [Trabace et al, 2002]. In a separate study, investigation of TNFa also showing an association with MO but not MA .…”
Section: Other Genesmentioning
confidence: 84%
“…In case of CSD (cortical spreading depression), for example, this process causes a local neurogenic inflammation with the activation of mast cells and macrophages, accompanied by the release of pro-inflammatory cytokines, ultimately leading to sensitization of meningeal nociceptive nerve endings [94]. For the COX-2, HLA-DRB1, LTA, TNFA, TNFB and TNFRSF1B genes, positive associations with migraines were detected [95][96][97][98][99][100][101][102].…”
Section: Inflammation and Genesmentioning
confidence: 99%
“…Peroutka et al [54] studied polymorphism frequencies for complement C3F and C3S in a sample of 137 migraineurs and found that this common polymorphism had no association with migraine susceptibility. Trabace et al [67] found that the frequency of TNFB*2 allele, located in the HLA class III region, was significantly increased and that of TNFB1 decreased in MO, suggesting that the TNFB*2 allele confers a high risk for MO. The same group had previously observed a protective role for the HLA-DR2 antigen in MA [68].…”
Section: Migraine and Genes Involved In Inflammationmentioning
confidence: 99%